The biomechanic origin of sprint performance enhancement after one-week creatine supplementation. - Schedel, J. M.; Terrier, P.; Schutz, Y. (Japanese Journal of Physiology, 2000)
In order to test whether an improvement of maximal sprinting speed after creatine (Cr) supplementation was due to the increase of stride frequency (SF), stride length (SL) or both, 7 subjects ran 4 consecutive sprints after 1 week of placebo or Cr supplementation. SF and SL were assessed by a triaxial accelerometer. Compared to the placebo, Cr induced an increase of running speed (+1.4% p < 0.05) and SF (+1.5%, p < 0.01), but not of SL. The drop in performance following repeated sprints was partially prevented by Cr. In conclusion, exogenous Cr enhanced sprinting performance by increasing SF. This result may be related to the recent findings of shortening in muscular relaxation time after Cr supplementation.